Analysis of User Satisfaction Level on PT. Semen Baturaja's Website Using the User Experience Questionnaire (UEQ) Method - Muhammad Hidayat; Helda Yudiastuti; Evi Yulianingsih; Tri Oktarina (Brilliance: Research of Artificial Intelligence, 2025)
This study aims to analyze user satisfaction with the website of PT Semen Baturaja by employing the User Experience Questionnaire (UEQ) method. As a digital representation of the company, the website plays a significant role in disseminating information, promoting products, and strengthening the overall corporate image. In today’s digital era, providing an optimal user experience is crucial to ensure that a website can effectively fulfill user expectations and needs. The UEQ method serves as a comprehensive tool for assessing user experience through six essential dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data were gathered by distributing structured questionnaires to a group of users who were randomly selected from visitors to the company’s website. The analysis revealed that the website excels in efficiency, indicating that users find it quick and responsive in performing tasks. Furthermore, the site received above-average scores in attractiveness, perspicuity, stimulation, and novelty, reflecting a visually appealing layout, ease of navigation, engaging elements, and creative features that enhance user interaction. However, the dependability dimension scored below average, highlighting concerns regarding the website’s consistency, reliability, and error management. These findings suggest that while the website performs well in several areas, enhancements in system stability and functional reliability are necessary. In conclusion, this study underscores the importance of continuously evaluating and refining website performance. The insights gained are expected to provide meaningful input for PT Semen Baturaja in its efforts to improve website quality and ensure a more satisfying and dependable user experience in the future.